Providing Mother's Own Milk in the Context of the NICU: A Paradoxical Experience. (August 2013) - Hurst, Nancy; Engebretson, Joan; Mahoney, Jane S.
Background: Mothers of very preterm infants continue to face challenges related to providing their expressed breast milk in the neonatal intensive care unit (NICU). Objective: This qualitative study sought to understand the experience of mothers of hospitalized very preterm infants related to their daily pumping routine during the NICU stay. Methods: Fourteen women who were pumping breast milk for their hospitalized infants were interviewed. Sequential, semistructured, audiotaped individual interviews were conducted at 2 different time points: within 2 weeks following delivery when the mothers were pumping only, and 4 to 6 weeks once breastfeeding had been initiated. Results: The central themes found were: becoming a "mother–interrupted" and negotiating a paradoxical experience of separation and connection. Unique to these findings were the paradoxical view of the pump as both a wedge and a link to their infants, the intense dislike the mothers had for the tasks required to provide their expressed breast milk, and diversionary tactics used during pumping sessions. Conclusion: The complexity of thoughts, actions, and behaviors revealed in the mothers' narrative accounts provides a guide to direct future breastfeeding interventions and management.